Mistaken Identifiers: Gene name errors can be introduced inadvertently when using Excel in bioinformatics - Barrett J Carl; Linehan W Marston; Uchio Edward; Bussey Kimberly J; Riss Joseph; Kane David W; Zeeberg Barry R; Weinstein John N (BMC Bioinformatics, 2004)
Abstract Background When processing microarray data sets, we recently noticed that some gene names were being changed inadvertently to non-gene names. Results A little detective work traced the problem to default date format conversions and floating-point format conversions in the very useful Excel program package. The date conversions affect at least 30 gene names; the floating-point conversions affect at least 2,000 if Riken identifiers are included. These conversions are irreversible; the original gene names cannot be recovered. Conclusions Users of Excel for analyses involving gene names should be aware of this problem, which can cause genes, including medically important ones, to be lost from view and which has contaminated even carefully curated public databases. We provide work-arounds and scripts for circumventing the problem.